Passive Identification is Non Stationary Objects With Closed Loop Control - Dyadik V. F. Valery Feodosievich; Nadezhdin I. S. Igor Sergeevich; Goryunov A. G. Aleksey Germanovich; Manenti F. Flavio (2016, 2016)
Title screen